Pengaruh Terapi Suportif Keluarga Terhadap Kemampuan Keluarga Merawat Klien Gangguan Jiwa di Kecamatan Bogor Timur - Damayanti, Rika; Hernawaty, Tati (Universitas Islam Negeri Raden Intan Lampung, 2014)
Mental illness experienced by 96 people between 12,392 people in Bubulak District, West Bogor. At the same time, family knowledge and abilities are not going well, services for psychological health programs by Community Health Centers are not going well, and Family Support Groups are not there. The title of this research is the Effect of Supporting Family Groups on Family Ability in Caring for Clients with Mental Illness in Bubulak Regency, West Bogor. This study aims to obtain a comprehensive picture of the influence of the Family Support Group on the ability of families to care for clients with mental illness. The study design used a quasi-experimental pre-post trial with a control group using the intervention of the Family Support Group. The sample was selected using a single-stage cluster and consisted of 74 families with a client mental illness. This group is divided into two groups as follows: Group I (Care of family support groups, four meetings consisting of 2 weeks) and Group II (without Family Support Groups). Family cognitive abilities, affective abilities, and psychomotor abilities were assessed using a questionnaire, and then the results of the questionnaire were analyzed using the dependent t-test, independent t-test, Chi-Square, and Simple Linear Regression methods. This study shows a significant increase in family cognitive abilities, affective abilities, and psychomotor abilities in caring for clients with mental illness. The ability of the group handled by the Family Support Group is significantly and significantly improved compared to the group without the Family Support Group. It is recommended to form and to conduct a Family Support Group to families who have clients with mental illness in the community.